Computational chemistry. reviews of current trends - Leszczynski, Jerzy, 1949- (World Scientific, 2003)
Chapter 1 of this volume provides an overview of the theoretical andnumerical aspects in the development of the polarizable continuummodel (PCM). Chapter 2 demonstrates a multiplicative scheme used toestimate the properties of two- and three-dimensional clusters from the properties of their one-dimensional components.